Literary and Political Background of Rampur State - Ali, Nisar; Mehmood, Sajid; Abbas, Syed Azwar (sourcecoder, 2022)
Rampur is considered as third school of poetry after Delhi and Luckhnow. Many prominent and legendary urdu poets of the time like "Dagh", "Ghalib"and "Ameer Minaee" joined the patronage of Rampur court. In the era of British rule in the subcontinent and where there was storytelling lyrics making and infect poetry love was prevailed. In that time several states got independence from the English and became independent. These states have seen the reign of various kings and Nawabs. Rampur was one of these important states it was considered in an important state due to its historical and literal status. A lot of literature writers poets ,kings and Nawabs norished the treasure of literature. Rohillass, Marathas,Jutes and other communities have ruled this era according to their wish and will. In this article, Rampur state's especial era from Aurang Zeb (1770) to Nawab Raza Ali Khan (1930), political customs and procedure of Princes,Nawab and Kings which effect the literature have been discussed and analyzed.